The Integration of the Islamic Education Hidden Curriculum in Character Building Based on the Panca Waluya Principles at SMK Budi Tresna Sumber Cirebon - Mukhammad Nawawi (PT Publikasiku Academic Solution, 2026)
Character education in vocational high schools faces significant challenges as educational institutions are expected to produce graduates who are not only technically proficient but also morally grounded, spiritually aware, and professionally responsible. This study aims to analyze and describe the integration of the Hidden Curriculum of Islamic Religious Education (PAI) in implementing the five pillars of Panca Waluya (Cageur, Bageur, Bener, Pinter, and Singer) as an effort to shape the character of students at SMK Budi Tresna Sumber Cirebon. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and document analysis. The results of the study indicate that the hidden curriculum is implemented through structured habituation programs such as Dhuha Prayer, Tadarus Al-Qur'an, and the 5S industrial culture (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) which effectively internalize spiritual values into work-ready professional characters. The main supporting factors include the role models (Uswah Hasanah) of educators, a conducive school environment ecosystem, and the positive influence of peers. However, this study also identified obstacles in the form of a lack of internal motivation of students, psychological challenges during puberty, as well as the influence of the external environment and lack of parental support that break the continuity of character at home. This study concludes that strengthening the synergy between schools and families and transforming external compliance into internal spiritual awareness is the key to the success of sustainable character education.